Relationship Between Nutritional Status And A Cough Classification Of Children Under Five Years In Public Health Center (Phc) Of Piyungan Bantul Yogyakarta - Masta Hutasoit; Latifah Susilowati (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2018)
Background: Cough or breathing difficulty is a common problem that causes the increased rate of mortality and morbidity in infants. According to the chart of Integrated Management of Childhood Illness (IMCI) in 2015 shows the difficulty in breathing or coughing is categorized into three cough diagnosis is not a cough but not pneumonia, pneumonia and severe pneumonia. Nutritional status of infants is important to forming body immune, especially in preventing infection. Malnutrition in infants results in children is vulnerable to various infections.Objective: Determining the relationship between nutritional status of under five years children and cough classification based IMCI in Public Health Center (PH) of Piyungan Bantul.Methods: The study was a descriptive correlational retrospective approach. Sampling technique by using simple random sampling. Subjects in this study amounted to 46 respondents, i.e children who come to the piyungan’s health center with complaints of cough in the period from June to August 2017. Data collection using secondary data by identifying the medical record data about weight and age and cough classification based IMCI. Results: The result showed the majority of nutritional status in both categories by 74%, the classification of a cough mostly not pneumonia at 69.6%. There was a relationship between the nutritional status of the classification of a cough in infants with a value of p = 0.001 (α <0.05) with the relationship (r) of -0.558 (medium). Conclusion: The hypothesis is acceptable. There is a significant relationship between nutritional status and classification of a cough by IMCI in PHC of Piyungan Bantul. It means better the nutritional status of children under five years making a lower classification of a cough in under five years children. Advice to parents is paying attention to nutrition for under five years children (micronutrients and macronutrients) who useful for the growth and development of them and improve the body's resistance to infection.